Identifikasi Kesulitan Siswa SMPIQU Al-Bahjah Pusat dalam Menyelesaikan Soal Operasi Bilangan Bulat dan Pecahan - Izatul Lailah, Shinta; Hamidah, Ida (STAI Al-Bahjah, 2023)
The purpose of this study was to find out the difficulties students experienced in solving integer and fraction operations in class VII students at SMIQu Al-Bahjah center. The type of research used is descriptive qualitative research and literature review with data collection techniques using diagnostic tests, interviews, and library data. Meanwhile, data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The subjects of this study were 32 students of class VII SMPIQu Al-Bahjah Center who completed diagnostic test questions. The results showed that (1) students did not understand the concept of integer operations, especially negative integer operations and mixed integer operations; (2) students experience problems in reading word problems and converting them into mathematical models; and (3) difficulties with fraction operations in algebraic.